Post-activation Potentiation: Effects of Different Conditioning Intensities on Measures of Physical Fitness in Male Young Professional Soccer Players - Petisco, Cristina; Ramirez-Campillo, Rodrigo; Hernández, Daniel; Gonzalo-Skok, Oliver; Nakamura, Fabio Y.; Sanchez-Sanchez, Javier (Frontiers in Psychology, 2019)
The aim of this study was to compare the effects of different post-activation potentiation (PAP) intensities on physical fitness of high-level male field soccer players. Athletes (n = 10; age: 21.6 ± 3.2 years) completed a control and PAP warm-ups in random and counterbalanced order. After control and experimental warm-up sessions participants completed a triple hop test with a dominant (H3Jd) and a non-dominant (H3Jnd) leg, a squat jump (SJ), a countermovement jump (CMJ), a non-repeated change of direction (COD) speed test (i.e., T test), a repeated sprint with a COD (RSCOD) test and a linear 30-m sprint test (S-30). The control warm-up (WU) protocol was designed according to athlete’s regular warm-up practice. The experimental PAP warm-ups included the same exercises as the WU, with addition of one set of half-back squats for 10 repetitions at 60%, 5 repetitions at 80%, and 1 repetition at 100% of 1RM (60%-PAP, 80%-PAP and 100%-PAP, respectively.) Threshold values for Cohen’s effect sizes were calculated and used for group’s comparison. Likely to most likely improvements were shown in H3Jd, H3Jnd, T-test, RSCODb and RSCODt only after the 80%-PAP protocol in comparison to the WU. Conversely, 100%-PAP and 60%-PAP protocols induced possible to most likely poorer performance in all jumps, the T-test and RSCODb in comparison to the WU. Possibly to most likely improvements were shown in all jumps, the T-test, RSCODb and RSCODt after the 80%-PAP warm-up protocol in comparison to the 100%-PAP and 60%-PAP warm-up protocols. A moderate PAP intensity (i.e., 80%-PAP) may induce greater improvements in jumping, repeated and non-repeated change of direction speed in male soccer players.